2012
DOI: 10.1016/j.clinph.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity measures predict olfactory processing speed in older adult carriers of the apolipoprotein E ε4 allele

Abstract: Objective The current study investigated the relationship between adiposity and P3 latency. Methods Fifty-one adults in two age groups (18-25 and 65+) participated. Odor stimuli were delivered via olfactometer as participants focused on a computer screen. Each stimulus was followed by presentation on the screen of four odor identification choices. Participants attempted identification by button press. Olfactory event-related potentials (OERPs) were recorded. BMI and waist circumference were measured as indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…No increased risk was present in lean ε4 carriers, or obese noncarriers. These findings extend previous reports on associations between BMI and APOE ε4 in the context of olfactory performance ( 43 ), and contribute to an emerging body of work reporting associations between BMI and ε4 in their consequences on brain function in old age. Both physical activity and gene-gene interactions have been implicated as modulating factors linking ε4 to dementia.…”
Section: Discussionsupporting
confidence: 88%
“…No increased risk was present in lean ε4 carriers, or obese noncarriers. These findings extend previous reports on associations between BMI and APOE ε4 in the context of olfactory performance ( 43 ), and contribute to an emerging body of work reporting associations between BMI and ε4 in their consequences on brain function in old age. Both physical activity and gene-gene interactions have been implicated as modulating factors linking ε4 to dementia.…”
Section: Discussionsupporting
confidence: 88%
“…A German study reported that abdominal obesity was inversely associated with grey matter volume, including the olfactory sulcus, although differences were not analysed according to stratification by sex 35 . In a study using an olfactometer, abdominal obesity was negatively correlated to olfactory processing speed in elderly females expressing the apolipoprotein E ε4 allele, a genetic risk factor for Alzheimer’s disease 36 . In our study, female subjects with abdominal obesity were more likely to experience olfactory dysfunction than those without.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic DNA was obtained from each subject using buccal swab of cheek cells and analyzed for the APOE genotype at an offsite laboratory as described in [67]. Data from 40 of these participants have previously been published [68]. …”
Section: Methodsmentioning
confidence: 99%